Changing the whole game: effects of the COVID-19 pandemic's accelerated digitalization on European bank staff's data protection capabilities - Ine van Zeeland; Jo Pierson (Financial Innovation, 2024)
Abstract The COVID-19 pandemic accelerated the acceptance of digital banking services such as online payment and banking apps. As bank clients become more likely to use online services and contactless payment, the amount of consumer data available for banks’ digitalization strategies has increased. This acceleration in digital banking has placed a spotlight on retail banks’ efforts to protect personal data. Bank staff are on the frontlines of both protecting personal data and communicating their banks’ efforts in this respect to maintain consumer trust. Our study aimed to answer the following question: How did the sudden increase in digitalization during the pandemic affect bank staff’s capabilities in protecting personal data? In a two-stage qualitative study, we collected empirical data on bank staff’s data protection efforts during accelerated digitalization. Analyzing our findings from the perspective of technological mediation theory, which focuses on the relationships between technologies, practices, and social arrangements, we found that in banking platformization, bank staff are disempowered in supporting clients, who are responsibilized for protecting themselves from fraud. Competitive pressures push retail banks into using client data in ways beyond sector norms, endangering the contextual integrity of data flows. Further, our findings show that digitalization presents bank clients with new risks, of which they are informed only after changing their banking practices, and it may be difficult to return to former arrangements. The application of mediation theory, combined with contextual integrity theory, clarified the shifting positions of different digital technology users in the infrastructural network of platformized banking and allowed for an in-depth analysis of conflicting interests. By clarifying these interests, difficulties were identified that need to be addressed in public policy and digital innovation projects to prevent loss of trust among bank clients.